'Look it Daddy'. (3rd August 2018) - Searles, Darcey K.
Abstract : Video-mediated technologies enable families with young children to participate in interactions with remote family members. This article examines how a family with young children uses the affordances of video conferencing to 'show' items or themselves. Findings indicate that there are two types of shows in these remote family interactions: those that are designed to receive identification, and those that are designed to receive appreciation and/or assessment. These shows are also often collaboratively produced between a child and her co-present parent. Finally, this paper considers the implications of these shows for our understanding of how families remotely participate in family life. Data are in American English.